Dietary, temporal and habitat resource partitioning by fou gekkonid lizards (sauria : gekkonidae) at Unimas campus, Kota Samarahan, Sarawak - Syazwan Affandi, Bin Zulkipli (Faculty of Resource Science and Technology, 2013)
A study of resource partitioning among four sympatric geckos species were conducted at UNIMAS campus over a period of three days. Four species were collected- Hemidactylus platyurus, Hemidactylus frenatus, Gehyra mutilata and Gekko monarchus. A total 46 specimens were collected to compare resource use in terms of diet, microhabitat and use of diel temporal resources. Berger-Parker Diversity Index, Diversity Index of Simpson (1949) and Mac Arthur and Levi’s (1967) were used to compute food dominance, niche breadth and niche overlap. Results show partitioning only for microhabitat and diel time, but not in dietary resources.